KONSTRUKSI SIMBOL TIKTOK SEBAGAI IDENTITAS DIRI REMAJA (STUDI FENOMENOLOGI PADA REMAJA DI KAYU AGUNG OKI) - Waldi Kurniawan (Jurnal Prodi Ilmu Komunikasi, 2023)
One of the impacts of globalization is the growing development of information and communication technology, one of which is marked by the existence of social media as a new digital world space that becomes the flow of information media as well as communication with a very wide reach/coverage. The ease of obtaining various kinds of information, expressing oneself, channeling talents and developing self-creativity is a plus that is presented by social media, one of which is TikTok. TikTok as a social media platform has quite a lot of impact on people's social life, especially teenagers, enabling its users to empower their creative minds by creating unique and interesting videos as a form of self-actualization, self-existence, and the formation of self-identity. The purpose of this study is to find out the construction of the TikTok symbol as self-identity and the meaning that is built about TikTok for adolescents at Kayu Agung OKI using symbolic interaction theory that is based on 3 concepts of thought. As for this study using qualitative research methods with data collection techniques namely observation, interviews, and documentation. The results of this study indicate that based on the concept of thinking as a basis in symbolic interaction theory, namely mind, self, and society.